Body mass index affecting ticagrelor monotherapy vs. ticagrelor with aspirin in patients with acute coronary syndrome: A pre-specified sub-analysis of the TICO randomized trial - Kim, Byung Gyu; Hong, Sung-Jin; Kim, Byeong-Keuk; Lee, Yong-Joon; Lee, Seung-Jun; Ahn, Chul-Min; Shin, Dong-Ho; Kim, Jung-Sun; Ko, Young-Guk; Choi, Donghoon; Hong, Myeong-Ki; Jang, Yangsoo (Frontiers in Cardiovascular Medicine, 2023)
Background Although ticagrelor monotherapy after 3-month dual antiplatelet therapy (DAPT) results in a significantly greater net clinical benefit over that with ticagrelor-based 12-month DAPT in patients with acute coronary syndrome (ACS), it remains uncertain whether this effect is dependent on body mass index (BMI). We aimed to evaluate the BMI-dependent effect of these treatment strategies on clinical outcomes. Methods This was a pre-specified subgroup analysis from the TICO trial (Ticagrelor Monotherapy After 3 Months in Patients Treated With New Generation Sirolimus-eluting Stent for Acute Coronary Syndrome), evaluating the interaction between BMI and treatment strategies for the primary outcome [composite of major bleeding and adverse cardiac and cerebrovascular events (MACCE): death, myocardial infarction, stent thrombosis, stroke, or target-vessel revascularization]. The secondary outcomes were major bleeding and MACCE. Results Based on a pre-specified BMI threshold of 25 kg/m2, 3,056 patients were stratified. Patients with BMI <25 kg/m2 had a higher risk of primary and secondary outcomes than those with BMI ≥25 kg/m2. Regardless of the BMI subgroup, the effects of ticagrelor monotherapy after 3-month DAPT on the primary outcome (pint = 0.61), major bleeding (pint = 0.76), and MACCE (pint = 0.80) were consistent without significant interaction compared with ticagrelor-based 12-month DAPT. The treatment effects according to the BMI quartiles and age, sex, and diabetic status were also consistent without significant interaction. Conclusion The BMI-dependent impact of ticagrelor monotherapy after 3-month DAPT compared with 12-month DAPT on clinical outcomes was not heterogeneous in patients with ACS. Clinical Trial Registration [www.ClinicalTrials.gov], identifier [NCT02494895].